PENGARUH SERVICE QUALITY DAN POSITIVE EMOTIONAL EXPERIENCE TERHADAP CUSTOMER SATISFACTION MELALUI ELECTRONIC WORD OF MOUTH PADA PENERIMAAN PESERTA DIDIK BARU DI LEMBAGA PENDIDIKAN ISLAM NURUL HIKMAH SIDOARJO - Binantoro, Patria Winahyu; Edy Sulistiyawan; Wira Yudha Alam (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Education plays a vital role in developing high-quality human resources that can compete in the era of globalization. Nurul Hikma Islamic Educational Institute in Arjo is one of the institutions that is constantly striving to improve the quality of its services to attract the attention of the masses, especially in the freshman admission procedure (PPDB). This study aims to analyze the impact of service quality and positive emotional experience on customer satisfaction directly and indirectly through electronic word of mouth (eWOM) as a parameter. A quantitative approach using partial least squares (PLS) structural equation modeling (SEM) method was conducted on 160 respondents, who were parents or guardians of children in preschool and primary school. The results show that service quality has a significant impact on both customer satisfaction and eWOM. On the other hand, positive emotional experiences have a significant impact on eWOM but have no direct effect on customer satisfaction. Furthermore, eWOM has been shown to have a significant impact on customer satisfaction and act as a mediator between service quality and parent satisfaction. These findings highlight the importance of improving service quality and creating positive emotional experiences to increase customer satisfaction and strengthen promotional strategies through social platforms.